Comparison of Two Types of Plating Media for Detection and Enumeration of Campylobacter from Poultry Samples - Line, J.E.; Berrang, M.E. (International Journal of Poultry Science, 2005)
Campy-Line agar, was compared to Campy-Cefex agar for recovery of Campylobacter spp. Five samples were examined from each of 18 broiler carcasses including: feathers, skin, crop, ceca and colon. An additional 16 rinse samples from fresh fully processed commercial broiler carcasses were also examined. Campy-Line agar provided Campylobacter spp. counts that closely mirrored those found by enumeration on Campy-Cefex agar. Campy-Cefex agar generally provided slightly higher counts (P<0.05) for all sample types except skin. However, Campylobacter populations recovered with Campy-Line agar were correlated with those recovered using Campy-Cefex agar; correlation coefficient values were 0.94 for feathers, 0.95 for skin, 0.98 for crop, 0.87 for ceca and 0.88 for colon samples. Observations suggest that Campy-Line agar is easier to use due to the virtual absence of contaminating colonies.